1993
DOI: 10.1213/00000539-199305000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary Response to Noxious Stimulation During Isoflurane and Propofol Anesthesia

Abstract: We studied the effects of noxious stimuli on arterial blood pressure, heart rate, pupil size, and the pupillary light reflex in 13 volunteers anesthetized with either isoflurane or propofol. Those given isoflurane (n = 8) were anesthetized twice, in a randomly selected order, once at an end-tidal concentration of 0.8% and once at 1.2%. An intense noxious stimulus was provided by electrical stimulation applied to skin of the abdominal wall (65-70 mA, 100 Hz). Hemodynamic values and pupillary responses were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
2
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 15 publications
(9 reference statements)
2
60
2
2
Order By: Relevance
“…We studied only one volatile agent (desflurane) and one -opioid agonist (fentanyl). However, other studies with PRD using the agents isoflurane (12) and propofol (18) have not revealed any differences in the reflex compared with what has been previously observed with the use of desflurane (15,20). Similarly, the depression of PRD has been shown to occur with other -opioid agonists such as remifentanil (3) and alfentanil (14).…”
Section: Discussionmentioning
confidence: 89%
“…We studied only one volatile agent (desflurane) and one -opioid agonist (fentanyl). However, other studies with PRD using the agents isoflurane (12) and propofol (18) have not revealed any differences in the reflex compared with what has been previously observed with the use of desflurane (15,20). Similarly, the depression of PRD has been shown to occur with other -opioid agonists such as remifentanil (3) and alfentanil (14).…”
Section: Discussionmentioning
confidence: 89%
“…33 Others did not find that esmolol reduced movement to command or pupillary response to noxious stimuli under anesthesia. 34,35 Why the contradictions?…”
mentioning
confidence: 99%
“…33 D'autres chercheurs n'ont pu affirmer que l'esmolol réduit le mouvement sur commande ou la réponse pupillaire à des stimuli nociceptifs sous anesthésie. 34,35 Comment expliquer ces contradictions ?…”
unclassified
“…Larson et al11 demonstrated the superiority of pupillometry for assessing nociception above vital signs during isoflurane and propofol anaesthesia. More recent research from Barvais and colleagues confirms those findings in volunteers during propofol anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the development of pupilometers with an integrated automated pupil tracking system,10 PDR can be used during surgical procedures in the operation room for nociceptive state evaluation 11, 12, 13…”
Section: Introductionmentioning
confidence: 99%